Cerebrospinal fluid and blood profiles of transfer RNA fragments show age, sex, and Parkinson's disease‐related changes. Issue 5 (22nd November 2022) - Paldor, Iddo; Madrer, Nimrod; Vaknine Treidel, Shani; Shulman, Dana; Greenberg, David S.; Soreq, Hermona
Abstract: Transfer RNA fragments (tRFs) have recently been shown to be an important family of small regulatory RNAs with diverse functions. Recent reports have revealed modified tRF blood levels in a number of nervous system conditions including epilepsy, ischemic stroke, and neurodegenerative diseases, but little is known about tRF levels in the cerebrospinal fluid (CSF). To address this issue, we studied age, sex, and Parkinson's disease (PD) effects on the distributions of tRFs in the CSF and blood data of healthy controls and PD patients from the NIH and the Parkinson's Progression Markers Initiative (PPMI) small RNA‐seq datasets. We discovered that long tRFs are expressed in higher levels in the CSF than in the blood. Furthermore, the CSF showed a pronounced age‐associated decline in the level of tRFs cleaved from the 3′‐end and anti‐codon loop of the parental tRNA (3'‐tRFs, i‐tRFs), and more pronounced profile differences than the blood profiles between the sexes. In comparison, we observed moderate age‐related elevation of blood 3'‐tRF levels. In addition, distinct sets of tRFs in the CSF and in the blood segregated PD patients from controls. Finally, we found enrichment of tRFs predicted to target cholinergic mRNAs (Cholino‐tRFs) among mitochondrial‐originated tRFs, raising the possibility that the neurodegeneration‐related mitochondrial impairment in PD patients may lead to deregulation of their cholinergic tone. Our findings demonstrate that the CSF and blood tRF profiles are distinct and that the CSF tRF profiles are modified in a sex‐, age‐, and disease‐related manner, suggesting that they reflect the inter‐individual cerebral differences and calling for incorporating this important subset of small RNA regulators into future studies. Abstract : Transfer RNA fragments (tRFs) are important regulatory small RNAs with diverse functions. We studied age, sex, and Parkinson's disease (PD) effects on the distributions of tRFs in the cerebrospinal fluid (CSF) and blood, in NIH and PPMI datasets. We discovered that CSF tRFs were more variable in length and cleavage subtypes, negatively correlated with age and showed more pronounced differences between males and females than blood tRFs. Both CSF and blood tRFs differentiated PD patients from controls, based on distinct subsets of tRFs, both highly enriched with mitochondrial Cholino‐tRFs. Our findings point at tRFs as a promising future biomarker.